Analyzing interactivity in asynchronous video discussions - Rothe, Hannes; Sundermeier, Janina; Gersch, Martin (Lecture Notes in Computer Science (LNCS), 2014)
Evaluating online discussions is a complex task for educators. Infor-mation systems may support instructors and course designers to assess the qual-ity of an asynchronous online discussion tool. Interactivity on a human-to-human, human-to-computer or human-to-content level are focal elements of such quality assessment. Nevertheless existing indicators used to measure inter-activity oftentimes rely on manual data collection. One major contribution of this paper is an updated overview about indicators which are ready for automat-ic data collection and processing. Following a design science research approach we introduce measures for a consumer side of interactivity and contrast them with a producer’s perspective. For this purpose we contrast two ratio measures ‘viewed posts prior to a statement’ and ‘viewed posts after a statement’ created by a student. In order to evaluate these indicators, we apply them to Pinio, an innovative asynchronous video discussion tool, used in a virtual seminar.
Keywords: asynchronous video discussion; educational data mining; higher education; interactivity; Online discussion